Image analysis techniques to estimate river discharge using time-lapse cameras in remote locations. (March 2015) - Young, David S.; Hart, Jane K.; Martinez, Kirk
Abstract: Cameras have the potential to provide new data streams for environmental science. Improvements in image quality, power consumption and image processing algorithms mean that it is now possible to test camera-based sensing in real-world scenarios. This paper presents an 8-month trial of a camera to monitor discharge in a glacial river, in a situation where this would be difficult to achieve using methods requiring sensors in or close to the river, or human intervention during the measurement period. The results indicate diurnal changes in discharge throughout the year, the importance of subglacial winter water storage, and rapid switching from a "distributed" winter system to a "channelised" summer drainage system in May. They show that discharge changes can be measured with an accuracy that is useful for understanding the relationship between glacier dynamics and flow rates. Highlights: We recorded river discharge in a remote area using a time-lapse camera. The camera is inexpensive and installation and operation are simple. Accurate edge-based image analysis leads to flow estimates. An 8-month record of a glacial outflow river in a rocky bed provides a case study. The measurements enable modelling of subglacial water storage and distribution.